Dynamics of soil microbial communities involved in carbon cycling along three successional forests in southern China - Hu, Minghui; Zhou, Shuyidan; Xiong, Xin; Wang, Xuan; Sun, Yu; Meng, Ze; Hui, Dafeng; Li, Jianling; Zhang, Deqiang; Deng, Qi (Frontiers in Microbiology, 2024)
Dynamics of plant communities during forest succession have been received great attention in the past decades, yet information about soil microbial communities that are involved in carbon cycling remains limited. Here we investigated soil microbial community composition and carbohydrate degradation potential using metagenomic analysis and examined their influencing factors in three successional subtropical forests in southern China. Results showed that the abundances of soil bacteria and fungi increased (p ≤ 0.05 for both) with forest succession in relation to both soil and litter characteristics, whereas the bacterial diversity did not change (p > 0.05) and the fungal diversity of Shannon-Wiener index even decreased (p ≤ 0.05). The abundances of microbial carbohydrate degradation functional genes of cellulase, hemicellulase, and pectinase also increased with forest succession (p ≤ 0.05 for all). However, the chitinase gene abundance did not change with forest succession (p > 0.05) and the amylase gene abundance decreased firstly in middle-succession forest and then increased in latesuccession forest. Further analysis indicated that changes of functional gene abundance in cellulase, hemicellulase, and pectinase were primarily affected by soil organic carbon, soil total nitrogen, and soil moisture, whereas the variation of amylase gene abundance was well explained by soil phosphorus and litterfall. Overall, we created a metagenome profile of soil microbes in subtropical forest succession and fostered our understanding of microbiallymediated soil carbon cycling.